THEORETICAL ASPECTS OF READINESS OF TEACHERS IN VOCATIONAL SCHOOLS TO IMPLEMENT STUDENT-CENTERED APPROACH - Hanna Tkachuk (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
This article deals with the problem of readiness for professional (educational) activity of teachers in vocational schools. The paper determines the relevance of readiness of teachers of special subjects of vocational schools to personality-oriented professional interaction with students and singled pedagogical conditions that determine this process. The analysis of psychological and pedagogical literature on the interpretation of the concepts of "readiness" and "commitment to the professional (educational) activities" is conducted. The features of this type of activity are revealed. It is determined that in the modern branch of science the phenomenon of readiness for professional work is studied at the personal, functional and personal-activity levels. The author suggests the generalized definition of "readiness for professional (teaching) activity" in the context of personal interaction between the participants of the educational process of vocational school.